Peran Sikola Mangkasara dalam Pembentukan Karakter Anak - Ilham, Nurul Muthmainnah (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study aims to find out: 1) What forms of coaching are done in Sikola Mangkasara. 2) What are the supporting and inhibiting factors of the training carried out in Sikola Mangkasara. This study uses a qualitative descriptive method, so in this study the researchers observed and interacted with Managers and coaches, coaches and instructors and the children of Sikola Mangkasara and by interviewing and reviewing their documentation. Where the approach technique used is a case study technique, using snowball sampling until the data needed is sufficient and accurate. The data analysis using analysis theory by Miles and Huberman. Based on the results of the research, it can be known that: 1) The Profile of Sikola Mangkasara, there are two point: a) A community social institution that exists as a container of coaching and energy empowerment of children and adolescents in a more positive direction. b) Able to be a special attraction with the program of coaching and training which is free to be given even scholarship for children every month.2) Forms of guidance conducted in Sikola Mangkasara in character building are carried out with various coaching activities that illustrate about there are several values that are taught and instilled in children such as religious values, politeness, self-confidence, discipline and independence, hard work, respect achievement and social sensitivity or concern. 3) Inhibiting factors in fostering and forming the character of Sikola Mangkasara's children is due to personal / innate factors of the family and social environmental factors, in this case there are many problems that violate existing values. Besides that there are supporting factors in the form of willingness and hard work from the manager and coaches in guiding children, by providing facilities in the form of places, facilities and scholarships, and starting to get support and positive responses from residents and parents of students. The role and existence of Sikola Mangkasara is obvious and very useful, it can be deduced by how the children's response with various things and positive changes that they feel during the coaching and training activities. Of course, the existence of Sikola Mangkasara is expected to contribute to the personal development and the character of children especially in children who are less attention or to be educated intentionally and sustainably.